Effect of static stretching on lactate removal after high intensity exercise - Young, J. C.; Pitt, K. T. (Medicine & Science in Sports & Exercise, 1996)
Active recovery more effectively lowers post-exercise lactate than does passive recovery. Since static stretching requires muscular effort while holding positions, it can be considered a form of active recovery. This study found that static stretching was more effective for promoting recovery than passive recovery but it was not as good as full active recovery. Implication: Static stretching would be a preferred recovery activity when no other form of active recovery can be performed.